2020
DOI: 10.1101/2020.06.17.156455
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Multilevel proteomics reveals host perturbations by SARS-CoV-2 and SARS-CoV

Abstract: The sudden global emergence of SARS-CoV-2 urgently requires an in-depth understanding of molecular functions of viral proteins and their interactions with the host proteome. Several omics studies have extended our knowledge of COVID-19 pathophysiology, including some focused on proteomic aspects 1-3 . To understand how SARS-CoV-2 and related coronaviruses manipulate the host we here characterized interactome, proteome and signaling processes in a systems-wide manner. This identified connections between the cor… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

25
325
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 173 publications
(351 citation statements)
references
References 99 publications
25
325
1
Order By: Relevance
“…Consistent with a robust signature for the glucocorticoid receptor across all CoVs (GR; q-values: SARS1, 3e-35; SARS2, 1e-35; MERS, 7e-32), while this paper was under review, studies were published showing the GR agonist dexamethasone was a successful therapeutic for SARS2 infection 31 . Finally, and also while this paper was under review, in vitro analyses confirmed our predictions of the modulation by SARS2 infection of ErbB/EGFR 20,32 and TGFBR 16,32 signaling systems (Fig. 2).…”
Section: To Illuminate Human Signaling Pathways Orchestrating the Trasupporting
confidence: 77%
“…Consistent with a robust signature for the glucocorticoid receptor across all CoVs (GR; q-values: SARS1, 3e-35; SARS2, 1e-35; MERS, 7e-32), while this paper was under review, studies were published showing the GR agonist dexamethasone was a successful therapeutic for SARS2 infection 31 . Finally, and also while this paper was under review, in vitro analyses confirmed our predictions of the modulation by SARS2 infection of ErbB/EGFR 20,32 and TGFBR 16,32 signaling systems (Fig. 2).…”
Section: To Illuminate Human Signaling Pathways Orchestrating the Trasupporting
confidence: 77%
“…ORF9b appears in UniProt annotations and was detected by Bojkova et al 14 infected cells 14,15 did not detect peptides that originate from the out-of-frame ORFs we annotated, likely due to challenges in detecting trypsin-digested products from short coding regions 24 . Indeed, two canonical SARS-CoV-2 proteins, ORF7b (43aa) and ORF-E (75aa) were also not detected by mass-spectrometry 14,15,26,27 , and our ribosome profiling data is the first to show these SARS-CoV-2 proteins are indeed expressed.…”
Section: Mainmentioning
confidence: 61%
“…They also indicate that it will not be trivial to identify the essential targets that mediate thapsigargin's antiviral effects. Our data provide a rich resource for further drug target analysis, also in conjunction with the few deep protein sequencing studies available for SARS-CoV-2 (but not MERS-CoV) (Bojkova et al, 2020;Bouhaddou et al, 2020;Grenga et al, 2020;Stukalov et al, 2020). Our study fills an important knowledge gap by providing a direct side-by-side comparison of pharmacologically targeted cells infected with two highly pathogenic human coronaviruses.…”
Section: Discussionmentioning
confidence: 88%
“…Green colors highlight HERPUD1 and BiP (HSPA5) values. Orange colors highlight SQSMT1 which was also identified as SARS-CoV-2regulated protein in an independent study (Stukalov et al, 2020). (D) Overrepresentation analysis showing the top 10 pathways mapping to gene IDs with increased (180 proteins, red) or decreased (61 proteins, blue) expression levels in thapsigargin-treated and infected cells compared to virus infection alone.…”
Section: Discussionmentioning
confidence: 99%